2016
DOI: 10.1371/journal.pone.0168727
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Endothelial and Tissue Responses to Cobalt Ferrite Nanoparticles and Hybrid Hydrogels

Abstract: Iron oxide nanoparticles (NPs) have been proposed for many biomedical applications as in vivo imaging and drug delivery in cancer treatment, but their toxicity is an ongoing concern. When NPs are intravenously administered, the endothelium represents the first barrier to tissue diffusion/penetration. However, there is little information about the biological effects of NPs on endothelial cells. In this work we showed that cobalt-ferrite (CoFe2O4) NPs affect endothelial cell integrity by increasing permeability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
0
14
0
2
Order By: Relevance
“…The compositions can be divided into natural, synthetic or combination of two classes [ 10 ]. Natural polymers are biocompatible, non-toxic and excellent carriers of drugs, in addition to biodegradability which is the inherent advantage of natural polymers [ 11 ]. However, natural polymer hydrogels have very weak mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…The compositions can be divided into natural, synthetic or combination of two classes [ 10 ]. Natural polymers are biocompatible, non-toxic and excellent carriers of drugs, in addition to biodegradability which is the inherent advantage of natural polymers [ 11 ]. However, natural polymer hydrogels have very weak mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Coverslips were mounted in fluoromount (Sigma-Aldrich), and pictures of stained cells were taken by fluorescence microscopy at 63× magnification. 44…”
Section: Methodsmentioning
confidence: 99%
“…Although, such nanomaterial may require a proper coating to confer adequate chemical stability and biocompatibility for biomedical applications. A major advantage of magnetogels is the reduction of nanoparticles toxicity, as shown by Finetti et al [ 98 ], who developed a magnetogel based on carboxymethylcellulose and CoFe 2 O 4 nanoparticles coated with (3-aminopropyl)trimethoxysilane acting as cross-linkers. The authors demonstrated that the endothelial permeability, oxidative stress, cytoskeleton organization and inflammatory markers associated with endothelial toxicity remained unchanged in magnetogels, while for the nanoparticles an increase was observed.…”
Section: Future Perspectives Goals and Conclusionmentioning
confidence: 99%